JURIDICAL IMPLICATIONS OF BUSINESS LICENSING REGULATIONS FOR OUTSOURCING COMPANIES POST CONSTITUTIONAL COURT DECISION NUMBER 91/PUU-XVIII/2020: IMPLIKASI YURIDIS PERATURAN PERIZINAN USAHA TERHADAP PERUSAHAAN OUTSOURCING PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 91/PUU-XVIII/2020 - Muhammad Jasmi; Muhammad Syafer; Muhammad Rafi Darajati Darajati (Constitutional Law Society, 2023)
In 2020 the Supreme Court received a request for a judicial review of the formal review of Law Number 11 of 2020 concerning Job Creation. One of the main contents of the application is outsourcing. The Constitutional Court issued Decision Number 91/PUU-XVIII/2020, which stated that the Job Creation Law was Conditionally Unconstitutional. One of the essences of the Constitutional Court decision is to suspend all strategic policies with broad implications, and it is not justified to issue new implementing regulations related to the Job Creation Law. The method in this research is a normative legal research method. Normative legal research is legal research conducted by examining literature or secondary data. This study uses a statute approach. The statute approach is research that prioritizes legal materials in the form of laws and regulations as essential reference material in conducting research. The results of the study show that Constitutional Court Decision Number 91/PUU-XVIII/2020 suspends all actions/policies that are strategic and have broad implications. It is not justified to issue new implementing regulations related to the Omnibus Law on Job Creation so that the Government cannot issue new implementing regulations and the implementation of outsourcing still refers to the old provisions, namely the Regulation of the Minister of Manpower Number 19 of 2012 and its amendments.